Faktor-Faktor Yang Berhubungan Dengan Pembelajaran Terhadap Hasil Ujian Skill Laboratorium Mata Ajar Keterampilan Dasar Praktek Klinik (KDPK) - Annisa Rahmidini (Jurnal Medika Cendikia, 2018)
With the evaluation of the results suggests educators can learn a main goal is to determine the level of success achieved by the students after participating in a learning activity, where the success rate is then marked with a scale value in the form of letters or words or symbols. If the primary purpose of the evaluation results of this study has been realized, then the result can be used and is intended for various purposes. The purpose of the psychomotor skills associated with the motor, the manipulation of objects or activities that require coordination of nerves and body coordination. From the research and processing of data is written, the authors can provide an outline of an explanation of these factors. Of the 40 number of students were respondents who did not pass the test lab skill KDPK much as 52.5%, while the pass in the test lab skill KDPK 47.5%. In learning internal factors that can affect the results of the test lab skill KDPK (theory test results, learning motivation, attitudes, self-concept, and intelligence) in which respondents are getting enough value (C) on the exam as much as 52.5% KDPK theory, motivated learn about as much as 47.5%, 47.5% refused attitude, a negative self-concept as much as 42.5% and the level of intelligence as much as 42.5% slow. Based on the factors related to the skill lab test results were eye Festive KDPK 1) exam results KDPK theory has a significant connection with the results of the eye exam skills of teaching KDPK, 2) motivation to learn has a significant correlation with the results of the exam skill lab teaching KDPK eyes, 3) attitude has a significant connection with the results of the eye exam skills teaching lab KDPK, 4) self-concept has a significant correlation with the results of the exam skill lab teaching KDPK eyes, 5) intelligence has a significant connection with the results of the exam skill lab teaching KDPK eyes. As an event that seeks to determine the level of student success in achieving the goals set, the evaluation of learning outcomes in the form of targeted domains contained in the destination. Realm of educational goals based on student learning outcomes can be generally classified into three namely anah cognitive, affective, and psychomotor domains. Keywords: learning, skills labs, clinical practice basic skills (KDPK)